Herding behaviour in mutual fund industry, evidence from Tehran Stock Exchange - Jafar Babajani; Javad Ebadi; Nasrin Moradi (مطالعات تجربی حسابداری مالی, 2015)
Behavioural finance approach gives us the possibility that in addition to the traditional concept of finance, human behaviour and psychological factors also result in variances in stock prices. In fact, this paper uses behavioural approach to transparency and understanding the impact of accidental and non-rational factors such as emotions on decision making process, to help decision makers.The research tries to answer these questions: Do mutual funds active in the Tehran Stock Exchange act according to herding behaviour? If they do, what kind of stocks (growth or value) and what kind of companies stock (in term of size, large or small) are the target of these acts? The hypotheses are as follows:− Mutual fund joint venture between herding behaviour exists in the Tehran Stock Exchange.− Herding behaviour of mutual fund is more common on smaller companies.− Herding behaviour of mutual fund shares on further growth.− Herding behaviour of mutual fund when purchasing less than sales growth is in stock.Herding behaviour of mutual fund when purchasing more than sales degrade is in stock